Risk Factors for Unilateral Trigeminal Neuralgia Based on Machine Learning - Ge, Xiuhong; Wang, Luoyu; Pan, Lei; Ye, Haiqi; Zhu, Xiaofen; Feng, Qi; Ding, Zhongxiang (Frontiers in Neurology, 2022)
Purpose: Neurovascular compression (NVC) is considered as the main factor leading to classical trigeminal neuralgia (CTN), and part of idiopathic TN (ITN) may be caused by NVC (ITN-nvc). This study aimed to explore the risk factors for unilateral CTN or ITN-nvc (UC-ITN), which have bilateral NVC, using machine learning. Methods: A total of 89 patients with UC-ITN were recruited prospectively. According to whether there was NVC on the unaffected side, UC-ITN patients were divided into two groups. All patients underwent a magnetic resonance imaging scan. The bilateral cisternal segment of the trigeminal nerve was manually delineated, which avoided the offending vessel (Ofv), and the features were extracted. Dimensionality reduction, feature selection, model construction, and model evaluation were performed step-by-step. Results: Four textural features with greater weight were selected in UC-ITN patients without NVC on the unaffected side. For UC-ITN patients with NVC on the unaffected side, six textural features with greater weight were selected. The textural features (rad_score) showed significant differences between the affected and unaffected sides (P < 0.05). The nomogram model had optimal diagnostic power, and the area under the curve (AUC) in the training and validation cohorts was 0.76 and 0.77, respectively. Ofv and rad_score were the risk factors for UC-ITN according nomogram. Conclusion: Besides NVC, texture features of the trigeminal-nerve cisternal segment and Ofv were also the risk factors for UC-ITN. These findings provided a basis for further exploration of the microscopic etiology of UC-ITN.